Unions and Decisionistic-Restricted Involvement in the CSR Debate – An Explanation to a Cooperative Approach - Zemla, Nataniel (Naše gospodarstvo/Our economy, 2019)
Corporate social responsibility (CSR) implies the responsibility of companies for sustainable management in economic, ecological and social terms. The majority of CSR works in science and research were written primarily with the focus on ethics (moral vs. market economy), bearer of responsibility (state vs. companies) and management (e.g. best practice, manuals). This article comes from the perspective of a stakeholder group that is constantly mentioned but receive insufficient attention: unions. Research indicated early on that unions leaned back in the European CSR-debate since its beginning 2001. Based on the case of German unions, the author will analyse their motivation by studying their statements. The systematic literature review provides the basis for his qualitative content analysis of reasonable motives. The results show the unions encountering a complex environment with diverse interests, in which it is difficult to position themselves. Furthermore CSR requirements placed on companies were considered, by economy, to be set very high. Although CSR is not driven by legal regulations, it unfolds quasi-binding rules. For those reasons, it is not surprising that unions were sceptical and restrictive. With its analysis of a defensive CSR strategy, the study contributes to progress in the field of engagement in international debates. The author deals in a theoretical-conceptual way with the existing research results in this field, invalidates them and presents his own attempt with explanation. His explanatory approach extends the existing explanatory patterns by a new perspective for the problem described.